CLIMATE ADAPTIVE REFORESTATION: EVALUATING INDIGENOUS SPECIES FOR DROUGHT AND FLOOD RESILIENCE - Khaled Al Sharqi; Mariam Al Mashani; Ali Al Shaibani (Yayasan Adra Karima Hubbi, 2026)
Reforestation is a crucial strategy for mitigating climate change, but the effectiveness of this approach is significantly influenced by the selection of tree species, especially in the face of extreme climate events such as droughts and floods. While traditional reforestation often focuses on non-native species, indigenous species offer greater resilience to local climate conditions. This study evaluates the potential of indigenous tree species for reforestation efforts aimed at improving ecosystem stability and enhancing drought and flood resilience. The main objective of this research is to identify indigenous species that exhibit superior adaptive traits for coping with fluctuating water availability in temperate and tropical ecosystems. A mixed-methods approach was used, combining field studies, ecological assessments, and laboratory experiments to analyze species’ growth patterns, survival rates, and physiological responses to water stress. The findings indicate that certain indigenous species, such as Xylia xylocarpa and Acacia mangium, show exceptional resistance to both drought and flood conditions, outperforming non-native species in long-term ecological health and carbon sequestration. The study concludes that integrating indigenous species into reforestation projects is crucial for building climate-resilient landscapes. This research contributes to advancing sustainable forest management practices by promoting species that are naturally suited to the challenges posed by climate change.